Periosteal Pedicle Flap Harvested during Vestibular Extension for Root Coverage - Shubham Kumar; Krishna Kumar Gupta; Rahul Agrawal; Pratima Srivastava; Shalabh Soni (Case Reports in Dentistry)
Root exposure along with inadequate vestibular depth is a common clinical finding. Treatment option includes many techniques to treat such defects for obtaining predictable root coverage. Normally, the vestibular depth is increased first followed by a second surgery for root coverage. The present case report describes a single-stage technique for vestibular extension and root coverage in a single tooth by using the Periosteal Pedicle Flap (PPF). This technique involves no donor site morbidity and allows for reflection of sufficient amount of periosteal flap tissue with its own blood supply at the surgical site, thus increasing the chances of success of root coverage with simultaneous increase in vestibular depth.